2017
DOI: 10.3892/ol.2017.6342
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intraperitoneal perfusion chemotherapy and response evaluation in patients with gastric cancer and malignant ascites

Abstract: Abstract. The present study describes the use of bidirectional chemotherapy in the treatment of patients with gastric cancer and peritoneal carcinomatosis (PC), using newly developed response criteria for the treatment of malignant ascites. In addition, the association between effusion response and survival was analyzed. Between June 2010 and May 2014, patients affected by malignant ascites secondary to unresectable PC of gastric origin were treated with a combination of systemic and loco-regional chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Studies have shown that HIPEC has good clinical efficacy in controlling ascites for patients with malignant ascites originating from peritoneal carcinomatosis. [ 2 , 13 , 14 ] In the present study, CRS+HIPEC and HIPEC+dCRS demonstrated a rather good efficacy in reducing malignant ascites and alleviating related symptoms. The total ascites objective remission rate was 100%, even though a complete CRS was not achieved in any patient in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Studies have shown that HIPEC has good clinical efficacy in controlling ascites for patients with malignant ascites originating from peritoneal carcinomatosis. [ 2 , 13 , 14 ] In the present study, CRS+HIPEC and HIPEC+dCRS demonstrated a rather good efficacy in reducing malignant ascites and alleviating related symptoms. The total ascites objective remission rate was 100%, even though a complete CRS was not achieved in any patient in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Studies showed that many primary or secondary intraperitoneal tumors such as gastric cancer, ovarian cancer, breast cancer, pseudomyxoma peritonei, or gastrointestinal stromal tumor could present a large amount of malignant ascites. [ 2 11 ] In the present study, CRC patients with malignant ascites included various pathological types such as well-differentiated adenocarcinoma, moderately differentiated adenocarcinoma, poorly differentiated adenocarcinoma, and mucinous adenocarcinoma or signet ring cell carcinoma. The results showed that there were no definite relationships between the formation of malignant ascites, tumor sites, and pathological types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that the graphene @VER-M or nano Fe 3 O 4 @VER-M system would be useful for mild PTT in the future. Or more succinctly, other kinds of heat treatments for cancer therapy such as hot compress 80 and hyperthermic perfusion 81 could be enhanced by forming hot compress@VER-M or hyperthermic perfusion@VER-M system.…”
Section: Discussionmentioning
confidence: 99%